(untitled) (Nepal Journal of Neuroscience, 2001)
Introduction: Recently, the International League Against Epilepsy (ILAE) has proposed new classification schemes for seizures and epilepsy. The applicability of these classification schemes has not been studied in resource-poor countries. Our aim was to find the relative frequency of different types of epilepsies in Kashmiri population presenting to the Department of Neurology, Superspeciality hospital. Materials and Methods: The data collected during the first visit included clinical details including details of seizure semiology. All patients had EEG and MRI BRAIN. All these data were used to classify seizure type and epilepsy using ILAE classification schemes. The ILAE 2017 epilepsy definition was used to diagnose epilepsy. The average annual incidence rates (AAIR) and 95% confidence intervals (CI) were calculated for epilepsies by onset and by etiology. Results: The present study was done on 500 patients with a mean age of 34.1±12.89 years. Majority of patients i.e. 151 (30.2%) were <10 years followed by ≥ 60 years in 138 (27.6%) patients, 10-20 in 118 (23.6%) patients. There were 60 (12%) patients who were aged between 40-60 years while 33 (6.6%) patients aged between 20-40. In our study participants, about 59.6% [n=298] had focal epilepsy, whereas 38.2% [n=191] had generalized epilepsy. About 2.2% [n=11] had unknown onset epilepsy. About 37% [n=185] of our participants had focal motor epilepsy, 22.6% [n=113] had focal non-motor epilepsy, 32.6% [n=163] had generalized motor epilepsy, and 28 [5.6%] patients had generalized nonmotor epilepsy. Conclusions: This study demonstrates that the ILAE 2017 classification of epilepsies can be applied in resource-poor countries with limited workup. Lesional epilepsies seen in this study is geographically specific to resource-poor countries.